Are altered states of consciousness detrimental, neutral or helpful for the origins of symbolic cognition? A response to Hodgson and Lewis-Williams. (February 2014) - Froese, Tom; Woodward, Alexander; Ikegami, Takashi
We respond to the commentaries by Hodgson and Lewis-Williams by clarifying the novelty of our theory. We argue that whenever Turing instabilities of neural activity play a role in generating visual hallucinations, they do more than shape the geometric patterns. Their relatively autonomous self-organization is a source of intrinsic value related to their self-maintenance as a pattern of activity, and they would also thereby decouple "higher-level" stages of neural processing from external stimulation, thus facilitating a more abstract mode of cognition. These additional features of our proposal support Hodgson and Lewis-Williams in their respective theories about the very first origins of human artistic activity. We also evaluate the critical literature regarding the possibility of ritualized enaction of altered states of consciousness (ASC) in early prehistory. We conclude that ASC were indeed possible, and suggest that they were likely involved in facilitating the social development of more symbolic forms of life and mind.